Cultivating Patriotism in Early Childhood Education: The "Angkasa Berbudaya" Program at Angkasa Adisutjipto Kindergarten - Izdihar Syifa Cahyani; Pamungkas, Joko (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
Fostering patriotism in early childhood is a critical challenge in an era of globalisation, where traditional values risk being overshadowed by modern influences. This study investigates the cultivation of patriotism in early childhood through the "Angkasa Berbudaya" program at Angkasa Adisutjipto Kindergarten in Yogyakarta, Indonesia. Employing a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving 20 students, five educators, and the school principal. The program integrates local culture, science, and technology to foster national identity while introducing global perspectives. Arts-based approaches, including traditional dance, angklung music, and marching bands, instil cultural appreciation, self-discipline, and creativity. Additionally, patriotism is embedded through national ceremonies, storytelling, and wearing traditional attire, promoting values like love for the homeland, discipline, and cooperation. Findings indicate that the program supports cognitive, social, and emotional development, contributing to a well-rounded education that balances tradition and modernity. However, challenges include inadequate facilities, limited parental involvement, and the absence of systematic evaluations to assess the program's long-term impact. Recommendations include improving resources, enhancing parental engagement, and incorporating broader multicultural perspectives to strengthen the program's effectiveness. This study underscores the significant role of culturally integrated education in fostering patriotism and social cohesion, offering a replicable model for early childhood education. By blending local heritage with global insights, the program prepares children to value diversity while maintaining a strong sense of national identity. Future research should focus on longitudinal impacts and scalable strategies for integrating patriotism into early education curricula.